Short‐ and long‐term perinatal outcome in twin pregnancies affected by weight discordance. (10th January 2017) - Vedel, Cathrine; Oldenburg, Anna; Worda, Katharina; Larsen, Helle; Holmskov, Anni; Andreasen, Kirsten R.; Uldbjerg, Niels; Ramb, Jan; Bødker, Birgit; Skibsted, Lillian; Sperling, Lene; Hinterberger, Stefan; et al.
Abstract: Introduction: The objective was to investigate the association between chorionicity‐specific intertwin birthweight discordance and adverse outcomes including long‐term follow up at 6, 18, and 48–60 months after term via Ages and Stages Questionnaire. Material and methods: In this secondary analysis of a cohort study (Oldenburg et al., n = 1688) and a randomized controlled trial (PREDICT study, n = 1045) twin pairs were divided into three groups according to chorionicity‐specific birthweight discordance: <75th percentile, 75th–90th percentile and >90th percentile. Information on infant mortality, admittance to neonatal intensive care units, and gestational age at delivery was available for all pairs. Detailed neonatal outcomes were available for 656 pairs from PREDICT, of which 567 pairs had at least one Ages and Stages Questionnair follow‐up. Logistic regression models were used for dichotomous outcomes. Ages and Stages Questionnair scores were compared using the method of generalized estimating equation to account for the correlation within twins. Results: The 75th and 90th percentiles for birthweight discordance were 14.8 and 21.4% for monochorionic and 16.0 and 23.8% for dichorionic twins. After adjustment for small for gestational age and gender, birthweight discordance >75th and >90th percentile was associated with induced delivery <34 weeks [odds ratio 1.71 (95% confidence interval 1.11–2.65) and odds ratio 2.83 (95% confidence interval 1.73–4.64), respectively]. Discordance >75th‐percentile was associated with an increased risk of infant mortality after 28 days [odds ratio 4.69 (95% confidence interval 1.07–20.45)] but not with major neonatal complications or with low mean Ages and Stages Questionnair scores at 6, 18, and 48–60 months after term. Conclusion: Chorionicity‐specific intertwin birthweight discordance is a risk factor for induced preterm delivery and infant mortality, but not for lower scores for neurophysiological development at 6, 18, and 48–60 months.